Press, publicity and masculinities through the Madrid newspaper El Álbum Ibero-Americano (1890-1909) - Simón Alegre, Ana I. (Universidad Pedagógica y Tecnológica de Colombia, 2021)
During the period between 1890 and 1909, the press played a crucial role in the dissemination of gender identities. It would be through the media of this era where the different expressions of masculinity and femininity were condemned, signaled, and promoted. In this investigation, the Madrid newspaper, El Álbum Ibero-Americano, is the principal source used in order to trace these alterations. The methodology used to localize the marks of these changes, above all those related to the masculine, has been to select the opinion articles most connected with the modifications in these gender paradigms. The information obtained from the analysis of these articles has been complemented with the localization of the advertising section of the newspaper, of products linked to these changes, such as Pastillas Bonald or the Polvos Coza. This research concludes that El Álbum Ibero-Americano was more than a feminine newspaper. From its pages, masculine alternatives were offered so that their readers would leave aside social expressions that were more typical of what from this medium was defined as «ugly sex» than of men who intended to live in an open society with parity between the sexes.